2016
DOI: 10.1128/aac.02872-15
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Membrane Influx and Efflux in Escherichia coli Sequence Type 131 Has an Impact on Bacterial Motility, Biofilm Formation, and Virulence in a Caenorhabditis elegans Model

Abstract: Energy-dependent efflux overexpression and altered outer membrane permeability (influx) can promote multidrug resistance (MDR). The present study clarifies the regulatory pathways that control membrane permeability in the pandemic clone Escherichia coli sequence type 131 (ST131) and evaluates the impact of efflux and influx modulations on biofilm formation, motility, and virulence in the Caenorhabditis elegans model. Mutants of two uropathogenic E. coli (UPEC) strains, MECB5 (ST131; H30-Rx) and CFT073 (ST73), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
3
19
0
Order By: Relevance
“…Comparison of the genomes of H 22 strain S250, H 30-Rx strain JJ1886, and H 41 strain SE15 showed high similarity in terms of the number and types of VF genes from the VFDB. This may explain the similar level of virulence that we found previously between H 22 strain S250 and an H 30-Rx strain in the C. elegans model [19, 42]. Nevertheless, strains S250 and JJ1886 displayed two different virotypes: D for strain S250 and C for strain JJ1886.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Comparison of the genomes of H 22 strain S250, H 30-Rx strain JJ1886, and H 41 strain SE15 showed high similarity in terms of the number and types of VF genes from the VFDB. This may explain the similar level of virulence that we found previously between H 22 strain S250 and an H 30-Rx strain in the C. elegans model [19, 42]. Nevertheless, strains S250 and JJ1886 displayed two different virotypes: D for strain S250 and C for strain JJ1886.…”
Section: Discussionsupporting
confidence: 83%
“…Biofilm formation was significantly delayed in the H 30-R strains. This is the first study to compare the formation of biofilms by H 22 and non-ESBL-producing H 30-R strains [4, 42, 44–46]. Further studies are required to verify the involvement of the fimB gene in the two different biofilm phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, our clade B strains were more frequently early biofilm producers than clade C strains (23, 24, 42). Knocking out the fimB gene in clade B strains resulted in loss of both early biofilm production capacity and early type 1 fimbriae expression.…”
Section: Discussionsupporting
confidence: 78%
“…In another study, the prevalence of biofilm production was significantly higher among ST131 than non-ST131 isolates regardless ESBL-production and antibiotic resistance (Kudinha et al, 2013). More refined analysis from Pantel et al has demonstrated largely diverse biofilm activity in E. coli ST131 clones (Pantel et al, 2016), as substantiated by others (Olesen et al, 2014;Shin and Ko., 2015). In this study, we also observed a strong relationship between ST131 strains and two virulence factors, fyuA and papGII, both of which, when absent, are significantly associated with biofilm production.…”
Section: Discussionmentioning
confidence: 78%